A Analisis Sentimen Ulasan Pengguna Aplikasi Tokopedia Berbasis Algoritma Naive Bayes Serta Pendekatan Klasifikasi Sentimen Positif Dan Negatif: - Pendahuluan, Metodelogi penelitian , Hasil dan pembahasan , kesimpulan - Aditiya, Rangga; Riffani, Sidik; Maulana, Faris; Amali (Jurnal SIGMA, 2024)
Changes in consumer behavior in shopping for daily necessities have driven the growth of e-commerce applications as the main platform for transactions. Tokopedia, as one of the leading e-commerce applications in Indonesia with a large number of users, is the main focus of this study. This study aims to analyze the sentiment of Tokopedia user reviews published on the Google Play Store using a data mining approach with Naive Bayes algorithm.Positive and negative sentiment classification methods are used to understand the views and evaluations of users on Tokopedia services. Review Data is extracted, processed, and trained using the Naive Bayes algorithm to classify reviews into positive or negative sentiments.